Structural insights on complement activation. (31st August 2015) - Alcorlo, Martín; López‐Perrote, Andrés; Delgado, Sandra; Yébenes, Hugo; Subías, Marta; Rodríguez‐Gallego, César; Rodríguez de Córdoba, Santiago; Llorca, Oscar
<x xml:space="preserve">Abstract</x> The proteolytic cleavage of C3 to generate C3b is the central and most important step in the activation of complement, a major component of innate immunity. The comparison of the crystal structures of C3 and C3b illustrates large conformational changes during the transition from C3 to C3b. Exposure of a reactive thio‐ester group allows C3b to bind covalently to surfaces such as pathogens or apoptotic cellular debris. The displacement of the thio‐ester‐containing domain (TED) exposes hidden surfaces that mediate the interaction with complement factor B to assemble the C3‐convertase of the alternative pathway (AP). In addition, the displacement of the TED and its interaction with the macroglobulin 1 (MG1) domain generates an extended surface in C3b where the complement regulators factor H (FH), decay accelerating factor (DAF), membrane cofactor protein (MCP) and complement receptor 1 (CR1) can bind, mediating accelerated decay of the AP C3‐convertase and proteolytic inactivation of C3b. In the last few years, evidence has accumulated revealing that the structure of C3b in solution is significantly more flexible than anticipated. We review our current knowledge on C3b structural flexibility to propose a general model where the TED can display a collection of conformations around the MG ring, as well as a few specialized positions where the TED is held in one of several fixed locations. Importantly, this conformational heterogeneity in C3b impacts complement regulation by affecting the interaction with regulators.